The detonator ([United States] : Sony Pictures Home Entertainment, 2006)
A Homeland Security agent takes no prisoners as he tracks down an international arms dealer who intends to set off a biological weapon within the United States.
Release date: Apr. 25, 2006.
Rating: R.; For violence, language and some nudity.
DVD.
Closed-captioned.
Keywords: Feature films; Video recordings for the hearing impaired